ANALISIS LAPORAN ARUS KAS SEBAGAI ALAT UKUR EFEKTIVITAS KINERJA KEUANGAN PERUSAHAAN DAERAH AIRMINUM (PDAM)KOTA TERNATE - Burhan Zakaria (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2021)
This study aims to determine how the financial performance of the Regional Water Company (PDAM) is assessed by using the cash flow statement and cash flow ratio. Data was collected by means of documentation and interview techniques. The objects in this study are balance data, income statements, cash flow statements, notes to financial statements, history and general overview of PDAM from 2014-2017. The research method uses descriptive analysis methods using cash flows from operating, investing, and financing activities as well as ratio analysis, namely Operating Cash Flow Ratio (AKO), Total Debt Ratio (TH), Cash Coverage Ratio to Current Debt (CKHL) and Ratio Capital Expenditure (PM). Based on the results of this study, the total cash flow of the company during the period 2014-2017 indicates that the company is in an illiquid condition when assessed in terms of its operational activities. With the ratio analysis that has been produced, it can be concluded that there is a decrease in cash flow, especially in operating activities every year and the company's ability to overcome its current liabilities has not been resolved. This shows that the Regional Drinking Water Company (PDAM) is in a bad position during the 2014-2017 period.